Facilitating SME Financing through Improved Credit Reporting - International Committee on Credit Reporting (World Bank, Washington, DC, 2015)
The general principles for credit reporting were issued by the World Bank in September 2011. Since then, the World Bank and the international committee on credit reporting (ICCR) have been leading efforts towards the implementation of the general principles worldwide. This report is one of the concrete outputs of the work following the general principles. It addresses one of the most significant problems that limit the ability of most small and medium enterprises (SMEs) around the world to obtain adequate external financing to underpin their productive activities: information asymmetries. Creditors assess the creditworthiness of credit and loan applicants based on two basic criteria: ones financial capacity or ability to repay a loan, and ones willingness to repay the loan. A credit reporting system s (CRS) basic objective is to address information asymmetries, which is crucial for determining repayment capacity and repayment willingness. Credit reporting can therefore be extremely valuable to creditors for enhanced, fact-based credit risk assessments, and in this sense can also be seen as a tool to facilitate access to financing, including by SMEs. The main objective of this report is therefore to identify actions that can be undertaken by authorities and other relevant policy makers to improve the flow of data and other relevant credit information on SMEs to creditors through CRS. For this purpose, the report first analyses the overall status of credit reporting activities in connection with SMEs.